Evaluation of five filter media in column experiment on the removal of selected organic micropollutants and phosphorus from household wastewater. (15th September 2019) - Zhang, Wen; Gago-Ferrero, Pablo; Gao, Qiuju; Ahrens, Lutz; Blum, Kristin; Rostvall, Ande; Björlenius, Berndt; Andersson, Patrik L.; Wiberg, Karin; Haglund, Peter; Renman, Gunno
Abstract: A bench-scale column experiment was performed to study the removal of 31 selected organic micropollutants (MPs) and phosphorus by lignite, xyloid lignite (Xylit), granular activated carbon (GAC), Polonite ® and sand over a period of 12 weeks. In total 29 out of the 31 MPs showed removal efficiency >90% by GAC with an average removal of 97 ± 6%. Xylit and lignite were less efficient with an average removal of 80 ± 28% and 68 ± 29%, respectively. The removal efficiency was found to be impacted by the characterization of the sorbents and physicochemical properties of the compounds, as well as the interaction between the sorbents and compounds. For instance, Xylit and lignite performed well for relatively hydrophobic (log octanol/water partition coefficient ( K ow ) ≥3) MPs, while the removal efficiency of moderately hydrophilic, highly hydrophilic and negatively charged MPs were lower. The organic sorbents were found to have more functional groups at their surfaces, which might explain the higher adsorption of MPs to these sorbents. The removal of several MPs improved after four weeks in sand, Xylit, GAC and lignite which may be related to increased biological activity and biofilm development. GAC and sand had limited ability to remove phosphorus (12 ± 27% and 14 ± 2%, respectively), while the calcium-silicate material Polonite ® precipitated phosphorus efficiently and increased the total phosphorus removal from 12% to 96% after the GAC filter. Highlights: Physicochemical properties of the compound are important for the adsorption process. The characteristics of the sorbents influence the removal rate. The removal mechanisms are affected by the interaction between sorbent and compound. Simultaneous removal of MPs and phosphorus occurs by combining GAC and Polonite ® .